Prognostic Value of Four Objective Nutritional Indices in Predicting Long-Term Prognosis in Elderly Patients with Atrial Fibrillation: A Retrospective Cohort Study - He Q; Fan X; Li B; He Q; Cao Y; Zhang H (Clinical Interventions in Aging)
Qingwei He,1,* Xingman Fan,2,3,* Bowen Li,3 Qiongyi He,1 Yukun Cao,2 Haitao Zhang1,2 1The Fifth School of Clinical Medicine, Air Force Clinical Medical School, Anhui Medical University, Hefei, Anhui, 230032, People’s Republic of China; 2Department of Cardiology, Air Force Medical Center, Air Force Medical University, PLA, Beijing, 100142, People’s Republic of China; 3Graduate School, Hebei North University, Zhangjiakou, Hebei, 075000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haitao Zhang; Yukun Cao, Email kjzht@sina.com; caoyukuntg@163.comBackground: Several objective and comprehensive nutritional assessment methods have been used for predicting adverse outcomes in elderly patients with various diseases. However, their predictive value for long-term adverse outcomes in elderly patients with atrial fibrillation (AF) is unclear. This study aimed to explore the prognostic significance of the four nutritional indices, namely Prognostic Nutritional Index (PNI), Geriatric Nutritional Risk Index (GNRI), Controlling Nutritional Status (CONUT), and High-Sensitivity Modified Glasgow Prognostic Score (HS-mGPS), in evaluating the long-term prognosis in elderly patients with AF.Methods: This retrospective study was conducted at a single center and included a total of 261 elderly patients with AF from December 2015 to December 2021. Patients were divided into all-cause death and survival groups based on the follow-up results. Kaplan–Meier analysis and COX regression were conducted to explore the relationship between all-cause mortality and nutritional scores. In addition, Receiver Operating Characteristic (ROC) curves were used to compare the predictive value of the four nutritional screening tools for the endpoint event.Results: During the follow-up period, 119 cases (45.59%) of all-cause mortality were recorded. The cumulative incidence of all-cause death was significantly higher in participants with a lower PNI, lower GNRI, higher CONUT, and higher HS-mGPS levels. And the low PNI (HR 1.325, 95% CI 1.032– 2.857, P=0.025) and the high HS-mGPS (HR 2.166, 95% CI 1.281– 4.326, P=0.023) groups were independently and significantly associated with increased risk of all-cause death analyzed by multivariate COX regression. Additionally, PNI showed the best area under the curve value (AUC: 0.696, 95% CI 0.632– 0.760 P < 0.001) for the prediction of all-cause mortality compared with the other nutritional indices.Conclusion: Among the four nutritional risk screening tools, PNI might be a simple and useful indicator in predicting the long-term prognosis of elderly patients with AF.Keywords: atrial fibrillation, AF, aged, mortality, nutrition, prognosis